Determinants of Financial Distress in Islamic Banks: Does Firm Size Matter? - Muhammad Zaki As Shafi MT (CV. Era Digital Nusantara, 2024)
This study examines the effects of Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (BOPO) on Financial Distress, with Firm Size as a moderating variable, in Indonesian Sharia Commercial Banks from 2019 to 2023. Using panel data from 10 banks analyzed using the Random Effects Model (REM), the findings reveal that only FDR significantly affects Financial Distress. A key discovery is that Firm Size significantly moderates (weakens) the negative impact of FDR on Financial Distress, providing empirical support for the